A conceptual framework for integrated performance management systems. Issue 3 (2nd September 2019) - Johanson, Ulf; Almqvist, Roland; Skoog, Matti
Abstract : Purpose: The purpose of this paper is to further develop a conceptual framework for analysing performance management systems (PMS). The framework aims to be useful for a rich understanding of a specific organisation's PMS. At the same time, it should preferable be simple so that it could be used even in practice. The framework adds to earlier work by Malmi and Brown (2008), Ferreira and Otley (2009), Broadbent and Laughlin (2009), Bedford and Malmi (2015) and Johanson et al. (2001). Design/methodology/approach: The paper is theoretical but has also been applied to a Swedish municipality. The purpose of the latter was to understand if the framework is feasible so far. Findings: The authors hold that the framework in its present form is useful to use as an analytical tool even if it needs to be subjected to further development. Research limitations/implications: The paper addresses an issue that is continuously changing. This means that the suggested framework may suffer from theoretical weaknesses in some respects. To balance between a theoretically deep and exhaustive framework and a framework that is simple enough to use is a tricky question that needs further investigation. Practical implications: The ambition with the framework is that it shall be useful even in practice. Originality/value: The need for further research in the PMS area has been emphasised by the above researcher but also by, e.g., Van Helden and Reichard (2016) . They hold that the authors need rich European cases to improve the understanding of how PMS works. The authors hold that the present framework has the potential to meet the demands from Van Helden and Reichard.